Revival: Volume II - Liptak, Andras; Szurmai, Zoltan; Harangi, Janos; Fügedi, Péter (Taylor & Francis Group, 2018)
Chemical synthesis of oligosaccharides is important to organic chemistry because of the critical biological functions of carbohydrates. Unfortunately, no handbook has been published on the subject...until now.